PERKEMBANGAN BALITA USIA 6-60 BULAN BERDASARKAN KEJADIAN ANEMIA DAN PEMBERIAN STIMULASI MELALUI PENDIDIKAN ANAK USIA DINI - Endah Puji Astuti (Universitas Jenderal Achmad Yani Yogyakarta, 2016)
Background: Children development is measured by four aspects; motoric skills, language, behavior, and mental development. Early childhood development was influenced by maternal nutrition during pregnancy, infant nutrition, stimulation, and parents’ knowledge. Objective: This study aimed to describe the development of children aged 6-60 months subject to anemia and stimulation through early childhood education. Method: The study was quantitative descriptive with 158 toddlers involved as respondents. Tools and materials used in this study were digital haemometer and DDST sheets. Result: Toddlers with normal development and suspect were majority experienced mild anemia (34.81%, 14,56%, respectively). While toddlers who followed early childhood education, majority had normal development (45.57%). Non-participating early childhood education tended to have developmental suspect (23.4%). Three toddlers with severe anemia (Hb 7.2 to 7.9 g%) had normal development, presumably due to early childhood education and one toddler with severe anemia (Hb 6 gr%) and not attending early education had suspected development. Conclusion: Toddlers with or without anemia had equal development, while toddlers who were given stimulation through early childhood education tended to have normal development. Key Word: Early childhood development, anemia, stimulation of early childhood education